Effect of luting materials and root third on glass fiber posts bonding strength after hydrothermal aging - Suellen Tayenne Pedrosa Pinto; Carlos Rangel de Moura Oliveira; Mário Tanomaru-Filho; José Maurício dos Santos Nunes Reis (PLoS ONE, 2026)
Statement of the problem Teeth with extensive coronal destruction face the challenge of retaining the restorative materials; however, glass fiber posts cemented with resin materials can help to address the issue. The retention of these posts depends on the bond strength to the dentin structure and may vary significantly along the root thirds. Purpose This study aimed to evaluate the effect of different luting materials and root thirds on the bonding strength of glass fiber posts to radicular dentin after hydrothermal aging. Materials and methods Seventy bovine incisors were divided into 7 groups (n = 10), according to the luting materials: Panavia V5 ( PV5 ), Rebilda DC ( RDC ), LuxaCore Z ( LCZ ), Allcem Core ( ACC ), RelyX Ultimate ( RXU ), RelyX U200 ( RXU200 ) or Fuji Plus ( FP ). After posts cementation, the roots were thermocycled (10,000 cycles; 5–55°C), sectioned into thirds, and tested for push-out bond strength (2.0 kN; 0.5 mm/min). Failure patterns were classified using a stereomicroscope, according to the material and root third. Data were statistically analyzed (α = 0.05). Results Bond strength significantly differed among root thirds for PV5 , ACC , RXU , and RXU200 (p < 0.05), while no significant differences were found for RDC , LCZ , and FP (p ≥ 0.05). PV5 and RXU exhibited the highest overall bond strength values. PV5 presented means of 14.97 ± 3.68 MPa (cervical), 11.08 ± 3.12 MPa (middle), and 10.47 ± 2.45 MPa (apical), while RXU showed 16.97 ± 4.22 MPa, 16.48 ± 3.61 MPa, and 6.51 ± 1.26 MPa, respectively. Overall, PV5 and RXU demonstrated superior and more consistent bond strength across root thirds, whereas the other cements displayed lower and more heterogeneous results. Conclusions The luting material influenced the bond strength of glass fiber posts to intraradicular dentin. Dual-cure resin cements with self-etch adhesive systems that contain functional monomers, such as PV5 and RXU , achieved more predictable adhesion, particularly in deep and complex regions. Clinical implications Analysis of bond strength and failure patterns supports clinical decision-making by identifying luting cements with superior retention, even in challenging regions, contributing to greater treatment longevity.